The Relationship between Body Image and Self-Confidence in Wearing Hijab Adolescents - Mursal, Maya Annisa; Murdiana, Sitti; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Cases of verbal sexual harassment, catcalling, are not serious crimes in Indonesia, so victims do not really know how to respond to the perpetrator, where the perpetrator's targets in this case are women, especially teenagers who are experiencing drastic changes in their body shape. This study aims to determine the relationship between body image and self-confidence in hijab-wearing teenagers who are victims of catcalling. The criteria for respondents in this study were teenagers who wore the hijab, aged 15 to 17 years, and were victims of catcalling. The subjects in this study were 100 teenagers wearing hijabs who were victims of catcalling. The sampling technique used is accidental sampling. This research uses quantitative methods with the Spearman Rho test. The results of this study show that there is a significant relationship between body image and self-confidence in hijab-wearing teenagers who are victims of catcalling (p = 0.000 < 0.05). The correlation coefficient between the body image variable and self-confidence is 0.938 and is classified as very strong. This research also shows that there is no difference in body image and self-confidence in hijab-wearing teenagers who are victims of catcalling based on age. This research provides implications for victims of catcalling to improve their body image and use self-confidence to face existing problems.